Exhaust toxicity evaluation in a gas turbine engine fueled by aviation fuel containing synthesized hydrocarbons. Issue 1 (26th June 2019) - Gawron, Bartosz; Białecki, Tomasz; Janicka, Anna; Zawiślak, Maciej; Górniak, Aleksander
Abstract : Purpose: The purpose of this paper is to examine the toxicological impacts of exhaust generated during the combustion process of aviation fuel containing synthesized hydrocarbons. Design/methodology/approach: Tests on aircraft turbine engines in full scale are complex and expensive. Therefore, a miniature turbojet engine was used in this paper as a source of exhaust gases. Toxicity was tested using innovative BAT–CELL Bio–Ambient Cell method, which consists of determination of real toxic impact of the exhaust gases on the human lung A549 and mouse L929 cells. The research was of a comparative nature. The engine was powered by a conventional jet fuel and a blend of conventional jet fuel with synthesized hydrocarbons. Findings: The results show that the BAT–CELL method allows determination of the real exhaust toxicity during the combustion process in a turbine engine. The addition of a synthetic component to conventional jet fuel affected the reduction of toxicity of exhaust gases. It was confirmed for both tested cell lines. Originality/value: In the literature related to the area of aviation, numerous publications in the field of testing the emission of exhaust gaseous components, particulates or volatile organic compounds can be found. However, there is a lack of research related to the evaluation of the real exhaust toxicity. In addition, it appears that the data given in aviation sector, mainly related to the emission levels of gaseous exhaust components (CO, Nox and HC) and particulate matters, might be insufficient. To fully describe the engine exhaust emissions, they should be supplemented with additional tests, i.e. in terms of toxicity.